Characterization, antioxidant potential and cytotoxic study of mangaba fruits - Carolina Fagundes Assumpção; Patrícia Bachiega; Maressa Caldeira Morzelle; David Lee Nelson; Eliane Augusto Ndiaye; Alessandro de Oliveira Rios; Éllen Cristina de Souza (Ciência Rural, 2014)
The mangaba (Hancornia speciosa) stands out and has a great potential for economic exploitation and researches have suggested relevant results regarding the nutritional and functional value of this food. Therefore, the objective of this study was to chemically and physicochemically characterize the mangaba fruit harvested in the Middle Araguaia region. It was evaluated the chemical composition, antioxidant activity, volatile compounds, preliminary photochemical studies of phenolic components and the cytotoxic potential of ethanolic extract fruits against Artemia salina. The mean pH, the total titratable acidity and the value for reducing sugars conclude that the mangaba possesses the characteristics appropriate for both fresh consumption and for processing. Between the mean values measured, the fruits presented high fiber content and a low caloric value. The analysis of the antioxidant potential revealed a significant activity and in the volatile compounds analysis, esters were the major class presents. The result of the phytochemical screening revealed that phenols, flavonoids and tannins were present in the ethanolic extract of mangaba and a significant activity in the cytotoxicity assay was observed.